2015
DOI: 10.3928/00904481-20150710-08
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in the Neonate: The Differential Diagnosis and Treatment

Abstract: Anemia is a common problem in the neonatal period. Presenting symptoms may suggest numerous possible diagnoses ranging from anemia seen as a normal part of development to anemia due to critical pathology. An illustrative case is presented to highlight the appropriate evaluation of the neonate with significant anemia. Several important features of the evaluation of neonatal anemia are highlighted. The constellation of signs and symptoms that occur in conjunction with the anemia are critical for the evaluation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…29 Ultimately, the clinical status of the neonate should be taken into consideration to prevent and treat end organ ischemia using specific protocols. 19,20,30,31 Our results call into question the trend of using a restrictive vs a liberal hematocrit strategy in neonatal blood management. Given that mild/moderate anemia in neonates has a strong independent association with mortality, consideration may be given to a target hematocrit level of 40% or more in high-risk infants (ASA status 3-5, weight ≤2 kg, preoperative mechanical ventilation, and inotropic support) to possibly minimize mortality associated with anemia.…”
Section: Discussionmentioning
confidence: 79%
“…29 Ultimately, the clinical status of the neonate should be taken into consideration to prevent and treat end organ ischemia using specific protocols. 19,20,30,31 Our results call into question the trend of using a restrictive vs a liberal hematocrit strategy in neonatal blood management. Given that mild/moderate anemia in neonates has a strong independent association with mortality, consideration may be given to a target hematocrit level of 40% or more in high-risk infants (ASA status 3-5, weight ≤2 kg, preoperative mechanical ventilation, and inotropic support) to possibly minimize mortality associated with anemia.…”
Section: Discussionmentioning
confidence: 79%
“…The conservative treatment for PKD is largely supportive in the clinic, including optimal red cells transfusion, iron chelation, and splenectomy as necessary . Gene therapy is under study as an alternative approach and has been demonstrated to be effective in animal models, but its application in humans is still limited .…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the hemolytic anemia in newborn infants should include blood typing of the mother and the infant and direct antiglobulin testing (DAT), to detect immune-mediated hemolysis. [29].…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Glycerol lysis and Pink tests are also used as first-line laboratory tests. Other more specialized tests for erythrocyte membrane defects include: flow cytometry, ektacytometry and SDS-PAGE of erythrocyte membrane proteins [28,29,46].…”
Section: Laboratory Diagnosismentioning
confidence: 99%